The war of the world twentieth-century conflict and the descent of the West - Ferguson, Niall (Penguin Press, 2006)
Historian Fergusson provides a revolutionary reinterpretation of the modern era that resolves its central paradox: why unprecedented progress coincided with unprecedented violence, and why the seeming triumph of the West bore the seeds of its undoing. From the conflicts that presaged the First World War to the aftershocks of the Cold War, the twentieth century was by far the bloodiest in all of human history. How can we explain the astonishing scale and intensity of its violence when, thanks to the advances of science and economics, most people were better off than ever before? Wherever one looked, the world in 1900 offered the happy prospect of ever-greater interconnection. Why, then, did global progress descend into internecine war and genocide? Drawing on a pioneering combination of history, economics, and evolutionary theory, Ferguson examines what he calls the age of hatred and sets out to explain what went wrong with modernity. --From publisher description.